2018
DOI: 10.1093/ons/opy268
|View full text |Cite
|
Sign up to set email alerts
|

A Connectomic Atlas of the Human Cerebrum—Chapter 14: Tractographic Description of the Frontal Aslant Tract

Abstract: In this supplement, we show a comprehensive anatomic atlas of the human cerebrum demonstrating all 180 distinct regions comprising the cerebral cortex. The location, functional connectivity, and structural connectivity of these regions are outlined, and where possible a discussion is included of the functional significance of these areas. In this chapter, we specifically address the regions integrating to form the frontal aslant tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…The FAT is a white matter fiber tract traveling in the coronal plane connecting the SFG to the ipsilateral IFG ( 27 ) ( Figure 2 ). According to the parcellation scheme developed by the Human Connectome Project (HCP), the FAT connects the SFG, in particular, two parcellations of the SMA complex (6ma and SFL) and two of the dorsolateral prefrontal cortex (8BL and S6-8) to the IFG (parcellations 44, 6r) and the frontal operculum (parcellations FOP1, FOP3, and FOP4) as well as the middle insula (MI) parcellation in the anterior insula ( 28 , 29 ). In line with the parcellation scheme, the tractography of the FAT shows terminations into the SFG, including not only the pre-SMA and SMA but also the lateral SFG ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAT is a white matter fiber tract traveling in the coronal plane connecting the SFG to the ipsilateral IFG ( 27 ) ( Figure 2 ). According to the parcellation scheme developed by the Human Connectome Project (HCP), the FAT connects the SFG, in particular, two parcellations of the SMA complex (6ma and SFL) and two of the dorsolateral prefrontal cortex (8BL and S6-8) to the IFG (parcellations 44, 6r) and the frontal operculum (parcellations FOP1, FOP3, and FOP4) as well as the middle insula (MI) parcellation in the anterior insula ( 28 , 29 ). In line with the parcellation scheme, the tractography of the FAT shows terminations into the SFG, including not only the pre-SMA and SMA but also the lateral SFG ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MI area lies in the posterior superior part of the short insular gyrus ( 39 ). The Human Connectome Project divided the insula in numerous parcellations ( 39 ) and found connections of the MI area with three SFG parcellations (6ma, 8BL, and SFL) through the FAT ( 29 ). The termination of the FAT in the insula has not been extensively studied, but Baker et al ( 39 ) noted that a previously known network, the salience network (SN), has as nodes both FAT terminations and the anterior insula.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal aslant tract (FAT) is a recently described WMT that runs orthogonal to the dominant direction of most tracts. 15 Connectomic mapping by our group and others suggests that the FAT has two primary functions: 1) link the supplementary motor area (SMA) to the premotor areas and area 44, and 2) link the middle cingulate portions of the salience network to the anterior insular portions. 15 Thus, it is not surprising that intraoperative FAT stimulation leads to language arrest while tractography studies have implicated FAT degeneration in nonfluent primary progressive aphasias.…”
Section: Observation 2: the Frontal Aslant Tract Is Eloquentmentioning
confidence: 98%
“…15 Connectomic mapping by our group and others suggests that the FAT has two primary functions: 1) link the supplementary motor area (SMA) to the premotor areas and area 44, and 2) link the middle cingulate portions of the salience network to the anterior insular portions. 15 Thus, it is not surprising that intraoperative FAT stimulation leads to language arrest while tractography studies have implicated FAT degeneration in nonfluent primary progressive aphasias. 16,17 In addition, recent data suggest that the FAT plays a key role in the genesis of postoperative SMA syndrome.…”
Section: Observation 2: the Frontal Aslant Tract Is Eloquentmentioning
confidence: 98%
“…Previous localizationist views have suggested that this deficit occurs primarily due to surgical insult in the posteromedial bank of the superior frontal gyrus, yet other patients too demonstrate varying degrees of mutism and hemiplegia when operating outside this canonical SMA (14). Fortunately, further insight on the major connectivity of the medial frontal lobe has revealed that the FAT is the principle pathway linking the SMA to premotor areas and area 44 (Broca's area) and also links hubs of the salience network, supporting a possible role of the FAT in initiating motor or speech activity through its interconnections throughout the initiation axis (87,88). We have recently shown that by applying this knowledge in patients with gliomas in the SMA, intraoperative identification and subsequent preservation of the FAT can reduce SMA syndrome compared to just "avoiding the posterior bank of the SFG" (Figure 2).…”
Section: Using Brain Network Maps In Surgerymentioning
confidence: 99%